EFFECT OF XYLAZINE ON TILETAMINE, ZOLAZEPAM ANAESTHESIA IN DOGS* - Mini Bharathan (Director of Academics and Research, Kerala Veterinary and Animal Sciences University, 1995)
The experiment was conducted to evaluate the effects of xylaznic on Tiletamine-Zolazepam anaesthesia in dogs. The study was conducted in 18 dogs divided into 3 groups. The first group was treated with Zoletil 5 mg/kg/i/v and second and third groups were given xylazine 0.5 mg/kg and l mg/kg i/m anti 15 min. later Zoletil 2.5 mg/kg and 1.25 mg/kg respectively i/v. The results indicated that xylazine had no synergistic effect on Tiletamine-Zolazepam anaesthesia but the side effects were less and muscle relaxation and analgesia was increased